Identification, isolation, and characterisation of bioactive compounds from Hypoestes aristata (Acanthaceae) and Leucosidea sericea (Rosaceae) - Selepe, Mamoalosi A. (University of Pretoria, 2021)
Thesis (PhD (Chemistry))--University of Pretoria, 2021.